Telling our stories: inside and outside of court - Shuy, Roger W. (Language and Law / Linguagem e Direito, 2018)
Linguists who serve as expert witness at trials are expected not only to present their technical analyses effectively but also to capture and hold the interest of the jury. This paper suggests that one way to increase jurors’ understanding of expert witness testimony and to increase their confidence in the expert is to contextualize their linguistic testimony by framing it as storytelling. However effective and accurate the testimony may be, it is better when it does not appear to be a disconnected fragment of the trial’s ongoing narratives (Barry, 1991). Instead, effective expert witnesses must try to be a part of the overall trial story by couching their technical analysis as much as possible in the form of a story with an Abstract, Orientation, Evaluation, and Coda (Labov and Waletsky, 1967). This paper suggests that forensic linguists practice their story telling skills outside the courtroom in order to hone their skills of story-telling at trial. Six of the author’s “war stories” are provided as examples.